Enhancing membrane repair increases regeneration in a sciatic injury model - Paleo, Brian J. (PLoS One, 2020)
Various injuries to the neural tissues can cause irreversible damage to multiple functions of the nervous system ranging from motor control to cognitive function. The limited treatment options available for patients have led to extensive interest in studying the mechanisms of neuronal regeneration and recovery from injury. Since many neurons are terminally differentiated, by increasing cell survival following injury it may be possible to minimize the impact of these injuries and provide translational potential for treatment of neuronal diseases. While several cell types are known to survive injury through plasma membrane repair mechanisms, there has been little investigation of membrane repair in neurons and even fewer efforts to target membrane repair as a therapy in neurons. Studies from our laboratory group and others demonstrated that mitsugumin 53 (MG53), a muscle-enriched tripartite motif (TRIM) family protein also known as TRIM72, is an essential component of the cell membrane repair machinery in skeletal muscle. Interestingly, recombinant human MG53 (rhMG53) can be applied exogenously to increase membrane repair capacity both in vitro and in vivo. Increasing the membrane repair capacity of neurons could potentially minimize the death of these cells and affect the progression of various neuronal diseases. In this study we assess the therapeutic potential of rhMG53 to increase membrane repair in cultured neurons and in an in vivo mouse model of neurotrauma. We found that a robust repair response exists in various neuronal cells and that rhMG53 can increase neuronal membrane repair both in vitro and in vivo. These findings provide direct evidence of conserved membrane repair responses in neurons and that these repair mechanisms can be targeted as a potential therapeutic approach for neuronal injury.